The Truman Show - Weir, Peter, 1944-; Carrey, Jim, 1962-; Harris, Ed, 1950-; Linney, Laura; Emmerich, Noah.; Paramount Pictures (Hollywood, CA : Paramount, 1998)
Truman's life is a fake. He lives in a big studio with hidden cameras everywhere. His friends and people around him are actors who play their roles in the most popular television series in the world: The Truman Show. He thinks he is an ordinary man and has no idea about how he is being exploited. What will he do when he finds out?
Originally released as motion picture.
Formatted to fit TV.
Director of photography, Peter Biziou; editor, William Anderson; music score, Burkhard Dallwitz.
Jim Carrey, Laura Linney, Noah Emmerich, Natascha McElhone, Holland Taylor, Ed Harris.
Rated PG.
VHS; hi-fi, stereo, Dolby surround.
Keywords: Feature films; Television programs -- Drama; Video recordings for the hearing impaired